Effect of Different Drying Methods on the Characteristics of Curcuma zedoaria rhizome (International Journal of Scientific Research and Management (IJSRM), 2024)
Curcuma zedoaria is one of the plants that has the potential to be developed as raw material for making traditional medicine. The results of the study showed that white ginger has diverse pharmacological activities such as antihyperglycemia, antihyperlipids, antihypercholesterol, antiviral, anticancer / antitumor, immunomodulators, analgetics, anti-inflammatory, antipyretic and antioxidants. In the production process of traditional medicines, the quality of simplicia used as raw materials must meet quality standards in order to provide a good therapeutic effect. The quality of white intersection simplicia can be influenced by several factors, one of which is the drying method. The purpose of this study was to determine the effect of drying method on the characteristics of white intersection simplicia. The drying methods studied are drying direct sunlight, greenhouse drying, wind and oven. The characteristics tested are organoleptis test, microscopic test, water soluble juice test, ethanol soluble juice, water content, total ash content, acid insoluble ash content, microbial and fungal contamination. The results showed that the drying method can affect the characteristics of Curcuma zedoaria simplicia. The greenhouse drying method produces simplicia with the highest levels of ethanol marine essence and watersoluble essence, respectively 10.97±0.013% and 13.86±0.110%. The lowest water content of simplicia using a 50oC oven is 5.48%. The lowest total ash content was with the hybrid method, namely 7.006±0.018%.